Creations - Havsteen, Sven Rune; Petersen, Nils Holger; Schwab, Heinrich W.; Østrem, Eyolf (Brepols, 2007)
The meanings of the noun ‘creation’, and the verb ‘to create’, range from the traditional theological idea of God creating <span class=